Ghana - Public Expenditures Review : Rural Water and Sanitation Sector - World Bank (Washington, DC, 2012)
The public sector review aims at supporting the Government of Ghana (GoG) in enhancing effectiveness and efficiency in the rural and semi-urban water and sanitation sub-sectors on the basis of an analysis of trends in sector development over the period 2001 to 2006. The present report provides a number of conclusions and recommendations that have been discussed with national stakeholders at a final workshop. On this basis a first draft of an action plan for moving towards a sector-wide (programme) approach (SWAP) in the sector has been formulated. Drinking water constitutes a priority in the Ghana poverty reduction strategy. Budgetary allocations to the rural water sub-sector have increased in real terms by more than three times over the past six years 2001-2006. On the whole, budgetary allocations to the sector increased by 36 percent in real terms per year over the observed period 2001-2006 due to increases in donor aid by an annual average of 68 percent in real terms per year. However, the level of domestic funding declined on average per year by 7 percent in real terms. Then, about 93 percent of the activities are funded by Development Partners. The relatively low GoG fiscal commitment is increasingly being questioned by Development Partners and it is being argued that GoG funding should at least cover a reasonable funding level of the government sector institutions. Finally, achieving the objectives for the sub-sector requires that organizational strengthening and capacity building is implemented within sector institutions, but especially at the district assembly (DA) level. The strengthening of the Water Directorate (WD) is vital in order to provide an adequate framework that will be in a position to spearhead the sector development and in particular the emergence of SWAP in the water supply sector. Community Water and Sanitation Agency (CWSA) plays an important role to ensure water delivery in an environment with relatively weak capacity at DA but needs to adjust its organizational structure and core functions to the decentralization process.